2016
DOI: 10.1016/j.biocel.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

PZP and PAI-2: Structurally-diverse, functionally similar pregnancy proteins?

Abstract: Pregnancy zone protein (PZP) and plasminogen activator inhibitor type 2 (PAI-2) are two multifunctional proteins that are elevated in normal pregnancy and numerous other inflammatory states. Both proteins were originally identified as protease inhibitors, but current evidence supports the notion that they may also function as modulators of T-helper cells and/or extracellular chaperones. Exacerbated inflammation, fibrinolytic disturbances and misfolded proteins are all implicated in the pathology of preeclampsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…For example, one of the top genes was PZP , pregnancy-zone protein gene, which had higher DNA methylation in the promoter and first exon region and lower gene expression in liver from males. PZP is known to inhibit proteinases and is upregulated in inflammatory conditions where it is believed to exert cellular-protective effects ( 52 ). Most plasma PZP is synthesized by the liver ( 53 ), and in agreement with our results, other studies have found higher serum levels of this protein in females ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the top genes was PZP , pregnancy-zone protein gene, which had higher DNA methylation in the promoter and first exon region and lower gene expression in liver from males. PZP is known to inhibit proteinases and is upregulated in inflammatory conditions where it is believed to exert cellular-protective effects ( 52 ). Most plasma PZP is synthesized by the liver ( 53 ), and in agreement with our results, other studies have found higher serum levels of this protein in females ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression in this cluster of Tph1 is consistent with a recent report that the majority of enterochromaffin cells in the mouse small intestine co-produce other gut hormones including PYY, GLP-1, and CCK [21] . The strongest marker of Cl3 was Pzp , an alpha2 macroglobulin of uncertain function [22] . Cl3 appeared distinct to the upper small intestine, as mRNA for Pzp was low in PPG-cells purified from the lower small intestine; a trend for higher expression in PPG-cells from the proximal compared to the distal intestine was also observed for another CL3 enriched gene Tph1 ( Figure S7 ), although this does not exclude that a relatively smaller sub-population of Pzp and/or Tph1 co-expressing cells is present in the more distal PPG population.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, SERPINB2 has been shown to reach to extracellular space. For example, SERPINB2 is secreted by endothelial cells in response to inflammatory stimulus, can move into extracellular space on surface of microparticles originating from cancer cells and is known to be present in the blood plasma during pregnancy . The function of extracellular SERPINB2 is to inhibit the extracellular protease urokinase plasminogen activator (uPA) and tissue plasminogen activator (tPA), which convert plasminogen to plasmin, a protease involved in extracellular matrix degradation and cell migration, macrophage invasion and adhesion, fibrinolysis and mediation of inflammation and tissue remodelling …”
Section: Introductionmentioning
confidence: 99%